The Effectiveness of Comic Strip in Improving Students’ Vocabulary and Reading Comprehension - Risma Azizah; Syifa Fadhilah Hamid (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
The purpose of this study was to discover there was a substantial effect of using comic strips on students’ vocabulary and reading comprehension in the tenth grade at SMK Lab Business School Kota Tangerang. The researcher used a quantitative method. In this study, pre-experimental research one-group pre-test post-test was used with 40 students as the sample, which was taken at non-random. The instruments for data collection were vocabulary and reading comprehension tests. The data distribution was not normal, so the researcher used Wilcoxon Signed Rank to analyze it. The Wilcoxon Signed Rank Test vocabulary and reading comprehension results of the above pre-test and post-test data were 0.000 less than 0.05. The mean score for the pre-test vocabulary was 58.12 and the mean score for the post-test vocabulary was 78.63. Meanwhile, the pre-test reading comprehension score was 58.12 and the post-test score was 78.63. It revealed a significant increase from the first to the second mean score. As a result, the findings of this study, which used comic strips to improve students’ vocabulary and reading comprehension in the tenth grade at SMK Lab Business School Kota Tangerang had a significant effect. This suggests that comic strips can be used as an alternative media in the process of teaching vocabulary and reading comprehension.Keywords: Comic Strip, Reading Comprehension, Vocabulary